Immune Profiling and Multiplexed Label‐Free Detection of 2D MXenes by Mass Cytometry and High‐Dimensional Imaging. Issue 45 (7th October 2022) - Fusco, Laura; Gazzi, Arianna; Shuck, Christopher E.; Orecchioni, Marco; Alberti, Dafne; D'Almeida, Sènan Mickael; Rinchai, Darawan; Ahmed, Eiman; Elhanani, Ofer; Rauner, Martina; Zavan, Barbara; Grivel, Jean‐Charles; et al.
Abstract: There is a critical unmet need to detect and image 2D materials within single cells and tissues while surveying a high degree of information from single cells. Here, a versatile multiplexed label‐free single‐cell detection strategy is proposed based on single‐cell mass cytometry by time‐of‐flight (CyTOF) and ion‐beam imaging by time‐of‐flight (MIBI‐TOF). This strategy, "Label‐free sINgle‐cell tracKing of 2D matErials by mass cytometry and MIBI‐TOF Design" (LINKED), enables nanomaterial detection and simultaneous measurement of multiple cell and tissue features. As a proof of concept, a set of 2D materials, transition metal carbides, nitrides, and carbonitrides (MXenes), is selected to ensure mass detection within the cytometry range while avoiding overlap with more than 70 currently available tags, each able to survey multiple biological parameters. First, their detection and quantification in 15 primary human immune cell subpopulations are demonstrated. Together with the detection, mass cytometry is used to capture several biological aspects of MXenes, such as their biocompatibility and cytokine production after their uptake. Through enzymatic labeling, MXenes' mediation of cell–cell interactions is simultaneously evaluated. In vivo biodistribution experiments using a mixture of MXenes in mice confirm the versatility of the detection strategy and reveal MXene accumulation in the liver, blood, spleen, lungs, and relative immune cell subtypes. Finally, MIBI‐TOF is applied to detect MXenes in different organs revealing their spatial distribution. The label‐free detection of 2D materials by mass cytometry at the single‐cell level, on multiple cell subpopulations and in multiple organs simultaneously, will enable exciting new opportunities in biomedicine. Abstract : "Label‐free sINgle‐cell tracKing of 2D matErials by mass cytometry and MIBI‐TOF Design" (LINKED) is a multiplexed label‐free single‐cell detection strategy enabling nanomaterial tracking and simultaneous measurement of multiple cell and tissue features. MXenes are designed to be detected within the mass cytometry range. Their detection and quantification are demonstrated in 15 human immune cell subpopulations and in different organs.